Proposal of Parasitaphelenchus dongguanensis (Fang, Zhao & Zhuo, 2002) n. comb. (Nematoda: Parasitaphelenchidae) - Kaisa, T.r. (Zootaxa, 2005)
Parasitaphelenchus dongguanensis (Fang, Zhao & Zhuo, 2002) n. comb. is proposed for Bursaphelenchus dongguanensis Fang, Zhao & Zhuo, 2002. Females are long (880–1720 µm) and slender (a=64–104), and have a short, conoid, mucronate tail. The vulva is located towards the posterior (V=86–92), and a vulval flap is absent. Oocytes are arranged in several rows and in a single row posteriorly. A long postuterine sac is present (34–119 µm). Males are 880 to 1230 µm long, and slender (a=84–134). The tail is short (c=48–102), straight, and bears three pairs of post-cloacal papillae. A small bursa envelops the distal portion of the tail. Spicules are small (8–13 µm), with a narrow, pointed rostrum and a well-developed, rounded apex. Spermatocytes are arranged in several rows. The stylet is 11 to 13 µm long and has small basal knobs. The cuticle bears fine, transverse striae, and there are four incisures in the lateral field.